Proteomics in predicting the prevalence of ovarian carcinoma: reality and hopes - Waksmański, Bogdan; Olejek, Anita (Menopause Review/Przegląd Menopauzalny, 2006)
Ovarian carcinoma remains a leading cause of deaths among carcinomas of the reproductive tract. Common diagnostic procedures are of limited efficacy, and they usually enable diagnosis when the disease is already advanced. This makes it necessary to search for more sensitive and more specific methods of detecting ovarian carcinoma at early stages. The profile of micro-molecular blood proteins reflects the pathological state of the organ, thus enabling to identify carcinoma at an early stage of its growth. Identification of such proteins in blood serum creates the basis for proteomics. The paper deals with contemporary approaches to the predicting of ovarian carcinoma based on the profile of proteins in subjects with ovarian carcinoma at early and advanced stages. Recent research regarding protein markers is discussed, which involves the comparison of protein profiles and the selection of indicator proteins, and then conventional analysing and reviewing of the behaviour of specific proteins, which often occur in negligible amounts, in various environments and different types of ovarian carcinoma.